Antiurolithiatic Activity of Gokhsuradi Churan, an Ayurvedic Formulation By In Vitro Method - Ashok Kumar Bagepalli Srinivasa; Lakshman Kuruba; Saleemulla Khan; Gopi Setty Saran (Tabriz University of Medical Sciences, 2013)
Purpose: Gokhsuradi churna is an ayurvedic formulation, was investigate for antiurolithiatic activity. Methods: Calcium oxalate crystallization was induced by the addition of 0.01M sodium oxalate solutions in synthetic urine and nucleation method. Results: The effect of Gokhsuradi Churna exhibited a concentration dependent inhibition of on calcium oxalate crystallization and nucleation. Conclusion: The present studies suggest that Gokhsuradi churna has a potential inhibition of calcium oxalate crystallization exhibited and nucleation. Gokhsuradi Churna showed potent antiurolethiatic activity.